Proximodistal Heterogeneity in Learning-promoted Pathway-specific Plasticity at Dorsal CA1 Synapses. (15th June 2020) - Paw-Min-Thein-Oo,; Sakimoto, Yuya; Kida, Hiroyuki; Mitsushima, Dai
Highlights: After contextual learning, we examined pathway-specific pre/post-synaptic plasticity in three CA1 subfields. Contextual learning induced plasticity in proximal and intermediate subfields at CA3-CA1 synapses. Contextual learning induced plasticity in intermediate and distal subfields at ECIII-CA1 synapses. The bilateral AP5 microinjections into the proximal or intermediate but not distal CA1 completely prevented the learning. Abstract: Contextual learning requires the delivery of AMPA receptors to CA1 synapses in the dorsal hippocampus. However, proximodistal heterogeneity of pathway-specific plasticity remains unclear. Here, we examined the proximodistal heterogeneity in learning-induced plasticity at the CA1 synapses with inputs from the entorhinal cortex layer III (ECIII) or from CA3. We subjected male rats to an inhibitory avoidance task and prepared acute hippocampal slices for whole-cell patch clamp experiments, where we stimulated ECIII-CA1 or CA3-CA1 input fibers to analyze evoked excitatory postsynaptic currents (EPSCs). Compared to untrained controls, trained rats exhibited higher AMPA/NMDA current ratios at CA3-CA1 synapses of proximal and intermediate, but not distal CA1 neurons, which suggested that region-specific plasticity occurred after learning. Moreover, trained rats exhibited higher AMPA/NMDA current ratios at ECIII-CA1 synapses of intermediate and distal, but not proximal CA1 neurons. These findings suggested the presence of proximodistal heterogeneity in pathway-specific postsynaptic plasticity. Regarding presynaptic plasticity, training slightly, but significantly increased the paired-pulse ratios of CA3-CA1 synapses of proximal and intermediate, but not distal CA1 neurons. Moreover, trained rats exhibited higher paired-pulse ratios at ECIII-CA1 synapses of intermediate and distal, but not proximal CA1 neurons, which suggested region-specific presynaptic plasticity. Finally, learning was clearly prevented by the bilateral microinjection of a plasticity blocker in the proximal or intermediate, but not distal CA1 subfields, which suggested functional heterogeneity along the proximodistal axis. Understanding region- and pathway-specific plasticity at dorsal CA1 synapses could aid in controlling encoded memory.